Neo-Victorianism: An Introduction - Smith, Michelle J. (Australasian Journal of Victorian Studies, 2013)
Neo-Victorian scholarship frequently adopts mirror metaphors to elucidate how contemporary literature and culture revises the nineteenth century. Simon Joyce, for example, though he does not apply the term neo-Victorian, uses the idea of a driver glancing into a car rearview mirror to show the way in which we can “never really encounter ‘the Victorians’ themselves but instead a mediated image” (4). His comparison emphasises that contemporary engagements with the Victorian prompt us to look forward into order to see what lies behind, and reminds us that this mirror image view is always a distortion. Ann Heilmann and Mark Llewellyn extend this understanding of neo-Victorian literature’s “reflective stance between our own period and that of the nineteenth century”, suggesting that its preoccupation with spectrality is “a reflection of our inability to recapture the Victorians” and describing the texts themselves as “simulations of the ‘real’” (144-45).